Pengaruh Rasio Keuangan terhadap Perubahan Laba pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia - Oktobryandra, Renaldy; Astuti, Tutut Dewi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of the investigation was to ascertain whether changes in company profits are affected by the current ratio., the margin of net profits, the return on assets, and the entire turnover of assets. Purposive sampling was used to gather data for this quantitative study, which focused on pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange between 2020 and 2022. The test utilized in this investigation was SPSS version 29, and the 30 samples were examined using the t test, multiple linear regression analysis, descriptive analysis test, and classical assumption test. The findings indicated that while total assets turnover, return on assets, and net profit margin significantly impacted deviations in corporate profits, the current ratio had no discernible impact.